Hydrofoils on pod for electrical propelled low speed vessels - Köhlberg, Dennis; Weingarten, Helena (My University, 2022)
The marine industry is facing changes, decreasing the emissions and environmental footprint of leisure and commercial vessels, implying imperative aspects to decrease the energy required to propel the vessel and the implementation of electrical propulsion systems. Hydrofoils have in the past been utilised to lift hulls out of the water, decreasing the energy required to propel the vessel, although this requires advanced system control. This project investigates the beneficial aspects of affecting the hull with a lift force at the stern, without lifting the entire hull out of the water at a primary speed of 15kn. The project develops concepts of hydrofoils implemented on the pod, focusing on a total lift-force of 7500N, decreasing the resistance of the hull up to 12%, evaluating and validating different characteristics and solutions. Starting the product development with an extensive design-space and decreasing it successively as information and knowledge are generated and gathered, concluding and scoring concepts to generate the concept catalogue of four concepts. These were concluded by performing extensive calculations regarding hull resistance with the method of Savitsky, and forces generated by wings/hydrofoils with generic equations and 2D-Computational Fluid Dynamics. During the development, material research and evaluation in regard to the concepts have extensively been explored and conducted. Concluding reinforced POM-C, aluminium alloys, and thermoset composites as viable materials for the developed concepts. Reinforced POM-C with the manufacturing method of injection moulding is concluded as the most cost-effective option, aluminium alloys with the manufacturing method of die casting as a recyclable option, and thermoset composites with the manufacturing method autoclave to enable complex geometrical designs with low weight and high strength. The result was concluded as four different concepts in the concept catalogue, accounting for their properties and characteristics. The concepts are the Single, Comes Around, Odd Dual, and Telescopic. The Single is characterised by its simplicity and low-risk design. Comes Around is characterised by its continuously swept wing, minimising vertices generated and increasing the efficiency. Odd Dual is characterised by decreasing the spaciousness while maintaining similar efficiency as the Single concept. Telescopic is characterised by its adjustable span width, enables the generated lift to be adjusted accordingly, and enables a compact product when operated in shallow waters.
Keywords: Hydrofoils, Foil, Electric propulsion, Pitch, Roll, Angle of Attack, Safety; Energy efficiency, Hull, Vessel, Conceptual development, Savitsky, Lift & Drag force